Chronic supplementation of omega-3 can improve body composition and maximal strength, but does not change the resistance to neuromuscular fatigue - Crestani, Dhiego Mangilli; Bonin, Érick Fernando Rodrigues; Barbieri, Ricardo Augusto [UNESP]; Zagatto, Alessandro Moura [UNESP]; Higino, Wonder Passoni; Milioni, Fabio [UNESP] (Springer Nature, 2017)
Purpose: The present study aimed to determine whether supplementation with omega-3 fatty acid (N-3) contributes to improving body composition, strength performance, and neuromuscular fatigue resistance in physically active men. Methods: The study was randomized, double–blind, and placebo controlled. 15 males were recruited and randomly assigned into two groups, N-3 supplementation (GN-3; N = 7) and placebo supplementation (GP; N = 8). Supplementation with N-3 or a placebo (safflower oil) was administered for 28-days at 1.4 g·day−1. During this period, physical activity was monitored (internal load = volume × perceived exertion scale). Before and after the supplementation period, body composition, one maximum repetition of knee extension (1RM), and maximum repetitions of knee extension with 70 % of 1RM load (RMs) pre and post an incremental running protocol until exhaustion were measured. Results: ANOVA two way (p < 0.05) revealed a decrease in body fat mass (GP before: 8.3 ± 2.1 kg × after: 7.7 ± 2.4 kg; GN-3 before: 12.8 ± 9.4 kg × after: 11.8 ± 9.3 kg), increase in lean mass (GP before: 61.8 ± 4.1 kg × after: 62.7 ± 3.9 kg; GN-3 before: 64.2 ± 5.8 kg × after: 66.2 ± 6.0 kg), and 1RM (GP before: 111.3 ± 29.1 kg × after: 111.3 ± 25.9 kg; GN-3 before: 115.0 ± 36.2 kg × after: 129.1 ± 39.9 kg) in the GN-3, without significant alterations in the GP and no interactions between-groups. Moreover, the absolute variation of the RMs pre and post the incremental running protocol were not significantly altered for both group (GP before: −1.1 ± 2.9 repetitions × after: −1.1 ± 2.6 repetitions; GN-3 before: −3.9 ± 2.9 repetitions × after: −5.0 ± 4.6 repetitions), with no interactions between-groups. Conclusion: Four weeks of N-3 supplementation seems to improved body composition and maximal strength of knee extension, without influencing neuromuscular fatigue resistance.
Keywords: Neuromuscular fatigue; Strength training; Weight lifting